Morphological and Histological Structure of Adexinal Glands of some Solitary Bee Species (Hymenoptera – Apoidea) - Mahmoud, Kariman M.; Shebl , Mohamed A. (Sociobiology, 2024)
Solitary bees are diverse and very important for plant and crop pollination. They are extensively studied taxonomically, but little is known about their anatomy and physiology compared to honey bees. Dufour’s gland is important for many physiological functions in social and solitary bees. The present study addresses the morphological and histological structure of Dufour’s gland in ten bee species representing bee families Andrenidae, Colletidae, Halictidae, Melittidae, Megachilidae, and Apidae. Results indicated that the shape and size of the glands tend to differ from one species to the other. However, on histological bases, the intern seems to be the same among the secretion cell types. The gland varied in length and size in the studied species, probably due to nesting behavior differences: ground and cavity nesting. Further studies are needed to clarify the different secretions produced by Dufour’s gland and their functions in each species.